Developing FAITHH: Methods to Develop a Faith-Based HIV Stigma-Reduction Intervention in the Rural South. Issue 5 (September 2018) - Bradley, Erin L. P.; Sutton, Madeline Y.; Cooks, Eric; Washington-Ball, Brittney; Gaul, Zaneta; Gaskins, Susan; Payne-Foster, Pamela
Human immunodeficiency virus (HIV) disproportionately affects Blacks/African Americans, particularly those residing in the southern United States. HIV-related stigma adversely affects strategies to successfully engage people in HIV education, prevention, and care. Interventions targeting stigma reduction are vital as additional tools to move toward improved outcomes with HIV prevention and care, consistent with national goals. Faith institutions in the South have been understudied as partners in HIV stigma-reduction efforts, and some at-risk, Black/African American communities are involved with southern faith institutions. We describe the collaborative effort with rural, southern faith leaders from various denominations to develop and pilot test Project Faith-based Anti-stigma Initiative Towards Healing HIV/AIDS (FAITHH), an HIV stigma-reduction intervention that built on strategies previously used with other nonrural, Black/African American faith communities. The eight-module intervention included educational materials, myth-busting exercises to increase accurate HIV knowledge, role-playing, activities to confront stigma, and opportunities to develop and practice delivering a sermon about HIV that included scripture-based content and guidance. Engaging faith leaders facilitated the successful tailoring of the intervention, and congregation members were willing participants in the research process in support of increased HIV awareness, prevention, and care.